Antecedents of Perceived Service Quality: Focus on Private Health Facilities in Ghana - Brobbey, Jackson Awuah (Journal of Biology and Life Science, 2022)
The main purpose of the study is to understand service quality in private healthcare facilities in Ghana. The study sought to find out factors affecting perceived service quality of private health facilities in Ghana. The study made use of a quantitative method which was in the form of an explanatory research design. Further to this, quantitative research was conducted with larger sample of two hundred and fifty (250) patients of private health care facilities. The researcher employed multiple regression analysis to analyze the data. The results of the study revealed that there was a positive and significant relationship between technical knowledge, provider responsiveness, effective leadership and collaboration. Among other important implications, the study recommended that, as a result of the positive and significant relationship established between the supported variables, stakeholders and management invest more into the training of hospital staffs in these critical areas of service delivery. Also, the study presented that, healthcare providers should be able to communicate with other professional in delivering healthcare.